Constituintes voláteis e atividade antimicrobiana de Senecio crassiflorus (Poir.) DC. var. crassiflorus - Murari, Anelise Levay (2007)
Several Senecio species (Asteraceae) have been used in folk medicine for the treatment of infections. This genus is rich in a wide variety of secondary metabolites such as alkaloids, flavonoids, and terpenoids with recognized antimicrobial activity. Senecio crassiflorus (Poir.) DC. var. crassiflorus, commonly known as margarida-das-dunas , is native from the South coast of Brazil and is known for containing pyrrolizidines alkaloids. This work describes the evaluation of the antimicrobial activity of the CH2Cl2 and EtOH extracts and essential oils of S. crassiflorus var. crassiflorus. Extracts were obtained by sequential maceration in CH2Cl2 and EtOH. The CH2Cl2 extract was firstly fractioned by CC over silica gel for the isolation of the sesquiterpene germacrene D, which was identified by GC-MS, 1H and 13C NMR. This compound no presents antimicrobial activity and it is considered a precursor of several other sesquiterpene derivatives. To essential oils analysis, two collections were carried out in the city of Capão da Canoa, one at the end of spring and the other one at the beginning of autumn. The essential oil of leaves, aerial and underground stems of Senecio crassiflorus var. crassiflorus was extracted by hydrodistillation and their analyses were performed by GC-MS. Their constituents were identified by the comparison of their retention indexes and their fragmentation patterns with literature data. The evaluation of the antimicrobial activity of the extracts and essential oils of S. crassiflorus var. crassiflorus was accomplished through the broth microdilution method based on M7-A6/CLSI/NCCLS document for anaerobic bacteria and M27-A2/NCCLS document for yeasts. Qualitative and quantitative differences have been found between the analyzed parts. The essential oil of the leaves was the most active against Gram-positive bacteria. None of the essential oils shown activity against Gram-negative bacteria, that allows to assign them bacterial activity of narrow specter. The CH2Cl2 extract of aerial steams showed good inhibitory activity against Staphylococcus aureus ATCC 25923 (MIC of 64 μg/mL and MBC of 512 μg/mL). The antibacterial activity from the oils collected at the beginning of autumn presented better action spectra. Only essential oil of the leaves showed activity antifungal.